The Important Role of Organizational Commitment, Competency and Work Capability in Improving Employee Performance - Marsudi Lestariningsih; Rismawati Rismawati (Trescode Green Organization, 2024)
This research aims to explore and analyze the relationship between organizational commitment, competence and work ability on employee performance at the Surabaya City Government Administration Bureau. With a quantitative and explanatory approach, data was collected through observations, questionnaires and documentation from 57 employees. Although the number collected was slightly reduced to 50 responses which could be analyzed using SPSS software. The results of the analysis show that there is a significant relationship between organizational commitment and increased employee performance. However, although competency and work ability have an impact on performance, the relationship is not significant. The implications of this research underline the importance of organizational commitment in improving employee performance in the government sector. By understanding that organizational commitment has a strong impact, management can focus more on strategies to strengthen employee commitment to increase efficiency and effectiveness in the Surabaya City Government Administration Bureau.